Infrared finite solutions for the gluon propagator and the QCD vacuum energy - Montero, J. C. [UNESP]; Natale, A. A. [UNESP]; Rodrigues Da Suva, P. S. [UNESP] (Elsevier, 1997)
Nonperturbative infrared finite solutions for the gluon polarization tensor have been found, and the possibility that gluons may have a dynamically generated mass is supported by recent Monte Carlo simulation on the lattice. These solutions differ among themselves, due to different approximations performed when solving the Schwinger-Dyson equations for the gluon polarization tensor. Only approximations that minimize energy are meaningful, and, according to this, we compute an effective potential for composite operators as a function of these solutions in order to distinguish which one is selected by the vacuum. © 1997 Elsevier Science B.V.